Computational fluid dynamic analysis of upper airway procedures in equine larynges - Tucker, Michelle L.; Wilson, David G.; Bergstrom, Donald J.; Carmalt, James L. (Frontiers in Veterinary Science, 2023)
Computational fluid dynamics (CFD) has proven useful in the planning of upper airway surgery in humans, where it is used to anticipate the influence of the surgical procedures on post-operative airflow. This technology has only been reported twice in an equine model, with a limited scope of airflow mechanics situations examined. The reported study sought to widen this application to the variety of procedures used to treat equine recurrent laryngeal neuropathy (RLN). The first objective of this study was to generate a CFD model of an ex-vivo box model of ten different equine larynges replicating RLN and four therapeutic surgeries to compare the calculated impedance between these procedures for each larynx. The second objective was to determine the accuracy between a CFD model and measured airflow characteristics in equine larynges. The last objective was to explore the anatomic distribution of changes in pressure, velocity, and turbulent kinetic energy associated with the disease (RLN) and each surgical procedure performed. Ten equine cadaveric larynges underwent inhalation airflow testing in an instrumented box while undergoing a concurrent computed tomographic (CT) exam. The pressure upstream and downstream (outlet) were measured simultaneously. CT image segmentation was performed to generate stereolithography files, which underwent CFD analysis using the experimentally measured outlet pressure. The ranked procedural order and calculated laryngeal impedance were compared to the experimentally obtained values. The CFD model agreed with the measured results in predicting the procedure resulting in the lowest post-operative impedance in 9/10 larynges. Numerically, the CFD calculated laryngeal impedance was approximately 0.7 times that of the measured calculation. Low pressure and high velocity were observed around regions of tissue protrusion within the lumen of the larynx. RLN, the corniculectomy and partial arytenoidectomy surgical procedures exhibited low pressure troughs and high velocity peaks compared to the laryngoplasty and combined laryngoplasty/corniculectomy procedures. CFD modelling of the equine larynx reliably calculated the lowest impedance of the different surgical procedures. Future development of the CFD technique to this application may improve numerical accuracy and is recommended prior to consideration for use in patients.